Predictors of successful recanalization following endovascular intervention in non-acute basilar artery occlusion - Liu, Ying; Wu, Zuoli; Wei, Shengwei; He, Wenbo; Ye, Weihao; Xu, Shang; Huang, Baozi; Qin, Chao; Gao, Wen; Ye, Ziming (Frontiers in Neurology, 2025)
ObjectiveThis study aims to identify factors influencing successful recanalization following endovascular intervention for non-acute basilar artery occlusion (NABAO).BackgroundEndovascular treatment (EVT) is a feasible approach for treating non-acute basilar artery occlusion, but it presents significant technical challenges due to the lack of standardized treatment protocols. Therefore, identifying patients most likely to benefit is critical to minimizing procedural risks.MethodsA retrospective analysis was conducted on 115 patients with NABAO treated via EVT. Factors associated with successful recanalization, including clinical symptoms, demographic characteristics, procedural outcomes, and imaging findings, were analyzed using multivariate analysis. A scoring system was developed based on independent predictors.ResultsSuccessful recanalization (defined as modified Thrombolysis in Cerebral Infarction [mTICI] ≥2b) was achieved in 81.7% (94/115) of cases. Multivariate analysis revealed that occlusion duration >3 months (odds ratio [OR]: 0.187, 95% confidence interval [CI]: 0.051–0.688, p = 0.012), blunt-shaped occlusion ends (OR: 0.236, 95% CI: 0.072–0.777, p = 0.018), occlusion length > 30 mm (OR: 0.144, 95% CI: 0.031–0.669, p = 0.013), and insufficient or absent distal compensation (OR: 0.25, 95% CI: 0.075–0.835, p = 0.024) were independent predictors of reduced technical success. The receiver operating characteristic (ROC) curve index for the scoring system, based on these independent predictors, was 0.817 (95% CI: 0.698–0.936, p < 0.001), with a sensitivity of 71.4% and a specificity of 85.4% at a cutoff of 2.5 points.ConclusionLonger occlusion duration (>3 months), blunt-shaped occlusion ends, occlusion length > 30 mm, and insufficient distal collateral compensation are independent negative predictors for successful recanalization in patients with NABAO treated via EVT. The proposed scoring system can help screen patients suitable for treatment and optimize treatment strategies, but further validation in prospective cohorts is needed.